Analysis on Economy of Green Industrial Building - Gan, Ying (Journal of Theory and Practice of Management Science, 2023)
Nowadays, people pay much attention to the development of green industrial buildings. Although green industrial buildings have many advantages in ecological protection and energy consumption, its economy is also the focus of people's attention. This paper mainly analyzes the economy of green industrial buildings based on the general situation of the project, for reference.